Transitional jobs after release from prison: Effects on employment and recidivism - Erin Valentine; Cindy Redcross (IZA Journal of Labor Policy, 2015)
This paper presents the results of two experimental evaluations of transitional jobs programs for recently released former prisoners: the Evaluation of the Center for Employment Opportunities (CEO) and the Transitional Jobs Reentry Demonstration (TJRD). The analysis assesses the effects of these programs on employment and recidivism. We find that the programs in both studies led to a large increase in employment driven by the transitional jobs themselves. However, the programs did not increase employment in non-program jobs. In addition, the CEO transitional jobs program reduced recidivism, but the TJRD programs did not. These results have implications for policy and research.
Keywords: J24; 330; Recidivism; Employment; Transitional jobs programs; Random assignment; Reentry